2016
DOI: 10.14202/vetworld.2016.1178-1183
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-anesthetic changes following administration of propofol alone and in combination of meperidine and pentazocine lactate in dogs

Abstract: Aim:The aim of this study is to find out the effect of propofol and its combination with meperidine and pentazocine lactate on certain clinico-anesthetic profiles in dogs.Materials and Methods:15 apparently healthy mongrel dogs of either sex of about 1 year of age were randomly divided into three groups of five dogs each. The animals of Group I were administered propofol intravenously alone “to effect,” whereas meperidine at 2 mg/kgb.wt. and pentazocine lactate at 2 mg/kg b.wt. were injected intramuscularly 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…and 28.00±2.00 sec. after administration of propofol alone and in combination with buprenorphine in dogs (Anandmay et al, 2012). Rapid onset of anaesthesia was recorded in all the three groups in the present study which might be due to the high lipid solubility of propofol and ability to rapidly cross blood-brain barrier.…”
Section: Clinical Parametersmentioning
confidence: 45%
See 1 more Smart Citation
“…and 28.00±2.00 sec. after administration of propofol alone and in combination with buprenorphine in dogs (Anandmay et al, 2012). Rapid onset of anaesthesia was recorded in all the three groups in the present study which might be due to the high lipid solubility of propofol and ability to rapidly cross blood-brain barrier.…”
Section: Clinical Parametersmentioning
confidence: 45%
“…Opioids in combination with propofol increase the probability of respiratory depression during anaesthesia (Short and Bufalari, 1999). Similarly, Anandmay et al (2012) also reported significant decrease in respiration rate after propofol alone and in combination with buprenorphine in atropinized dog. Severe respiratory depression was recorded in group DP due to synergistic effect of dexmedetomidine and propofol.…”
Section: Respiration Rate (Breaths Per Minute)mentioning
confidence: 82%
“…Animals in all the three groups showed smooth transition with no paddling (score 0) to occasional, slow paddling (score 1) movements while induction stage. Lower induction time noticed in group-T and group-P might be due to synergistic effect of opioids and propofol (Anandmay et al, 2016).…”
Section: Quality Of Inductionmentioning
confidence: 84%
“…Pentazocine is used to control mild to moderate postoperative pain. Pentazocine is more or less tolerable in most Dogs but acute toxicity may result in sinus tachycardia, hypotension, hypoventilation and Nystagmus [8].…”
Section: Introductionmentioning
confidence: 99%